Guiding Light: Selection from the Holy Quran (American Journal of Islam and Society, 1985)
TranslationIn the name of Allah, most benevolent, ever-merciful. 19. Truly man was created Very impatient;20. Fretful when evilTouches him;Good reaches him;22. Not so those decotedTo prayer;23. Those who remain steadfastTo their prayer;24. And those in whose wealthIs a recognised right;25. For the (needy) who asksAnd him who is prevented(For some reason from asking);26. And those who holdTo the truth of theDay Of Judgment;27. And those who fearThe displeasure of their Lord, . . .29. And those who guardTheir chasity, . . . ;32. And those who respectTheir trusts and covenants;33. And those who stand firmIn their testimonies;34. And those who guard(The sacredness) of their worship;35. Such will beThe honoured onesIn the Gardens (of Bliss). Surah LXX.For behavioral scientists, especially psychologists and psychiatrists, mostof whom these days are preoccupied with wide-spread psychological anxietiesand suicidal behavior, the Qur'an in this part of Surah al Ma'arij proposescertain traits and qualities of man which counter human fears and anxieties.It is the duty of Muslim behavioral scientists in general and psychiatrists inparticular to study and research these Qur'anic directions and propositionsabout human nature, and the traits, habits and behaviors necessary to countertheir negative effects on human life, peace and mind and gratification. It istheir duty to make people understand the important role of these Qur'anic directionsin human life and suggest the ways and means to the Muslims to develop ...